Comparing the effectiveness of teaching cognitive and metacognitive strategies on academic buoyancy - Khojasteh Abbasi, Farzaneh; Tarverdizadeh, Hajar; Younesi, Seyed Jalal (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: The present research was designed and implemented to compare the effectiveness of teaching cognitive learning strategies and metacognitive learning strategies on the academic buoyancy of Tehran students in the academic year 2020-21. Methods: The current research was conducted as a quasi-experimental study with a pre-test and post-test along with a control and follow-up group. The research population included students who were studying in Tehran in 2021; A random sampling method was used to select the sample. They were replaced in the test 1 and test 2 groups and the control group. First, the pre-test was performed for all three groups, then one training group was taught cognitive learning strategies and the other experimental group was taught metacognitive learning strategies; However, there was no intervention in the control group, and at the end, a post-test was taken from all three groups. The questionnaire used in the research was the Academic Buoyancy Questionnaire by Martin and Marsh (2008). To analyze the data, the method of mixed variance analysis was used. Results: The interaction of stages with the experimental group was effective in three stages of measurement in academic monitoring (F=8.78, P=0.001). Conclusion: The results showed that according to the average scores of the pre-test and post-test and comparing them with the control group, the academic buoyancy of the students has increased; Also, a follow-up test was taken after one month, in which the post-test changes remained stable and stable.